Khảo sát khả năng hấp phụ amoni của oxit phức hợp LaFeO3 kích thước nanomet. - Hà Chi, Nguyễn Thị; Dũng, Đoàn Trung; Chức, Phạm Ngọc; Bắc, Nguyễn Quang; Lịm, Dương Thị; Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2017)
Base on gel combustion method using polyvinyl alcohol under optimum condition such as gel-formation temperature of 80 oC, pH 4, molar ratio metal/PVA of 1/1, molar ratio La/Fe of 1/1, and calcination temperature of 550 oC for 2 hours, the nano-mixed oxide LaFeO3 was successful synthesized with average size of 100 nm. The prepared material was characterized by X-ray diffraction and scanning emission microscope. An investigation on the ammonium adsorption was illustrated with maximum adsorp ability of 19.88 gN/g at time equilibrium of 90 min. The adsorption capacity of the material did not depend on pH, Mn (II) and Fe(III). Keywords. LaFeO3, combustion method, polyvinyl alcohol, ammonium adsorption.